(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the unique features of tongue twisters involving color terms in English and Uzbek languages. The study highlights their linguistic structures, semantic functions, and cultural significance. Comparative analysis reveals similarities and differences in the use of color terms in tongue twisters across these languages. English tongue twisters tend to focus on phonetic complexity, while Uzbek ones emphasize rhythm and cultural values. This research provides insights into how color terms reflect linguistic creativity and cultural identity in both languages.